Nanohydrotalcite Supported Ruthenium Nanoparticles: Highly Efficient Heterogeneous Catalyst for the Oxidative Valorization of Lignin Model Compounds. Issue 31 (6th November 2017) - Baguc, Ismail Burak; Celebi, Metin; Karakas, Kadir; Ertas, Ilknur Efecan; Keles, Muhammed Nuri; Kaya, Murat; Zahmakiran, Mehmet
Abstract: The catalytic transformation of lignocellulosic biomass derived chemicals into value‐added chemicals under mild conditions remains a challenge in the fields of synthetic chemistry and catalysis. Herein, we describe a new heterogeneous catalyst system that efficiently works in the oxidative valorization of lignin model compounds. This new heterogeneous catalyst system comprised of nano‐sized hydrotalcite ( n ‐HT; Mg6 Al2 (CO3 )(OH)16 ) supported ruthenium(0) nanoparticles (Ru/ n ‐HT) was prepared by ion‐exchange of [Ru(OH2 )Cl5 ] 2− anions with the extraframework CO3 2− anions of n ‐HT followed by their borohydride reduction (NaBH4 ) in water at room temperature. The characterization of Ru/ n ‐HT was done by the combination of various spectroscopic and the sum of their results revealed that the formation of well‐dispersed ruthenium(0) nanoparticles with a mean diameter of 3.2 ± 0.9 nm on the surface of n ‐HT structure. The catalytic performance of Ru/ n ‐HT in terms of activity, selectivity and stability was tested in the aerobic oxidation of cinnamyl, veratryl and vanillyl alcohols, which are important lignin model compounds used to mimic the propyl side chain, the phenolic and non‐phenolic, respectively functional groups of lignin. We found that Ru/ n ‐HT nanocatalyst displays remarkable activity at high selectivity and almost complete conversion in these catalytic transformations under mild reaction conditions (at 373 K under 3 bar initial O2 pressure). Abstract : Ruthenium nanoparticles stabilized by nanohydrotalcite framework (Ru/ n ‐HT) were found to be highly efficient nanocatalyst for the oxidative valorisation of cinnamyl, vanillyl and veratryl alcohols in toluene under mild reaction conditions (at 353 K and under 3 bar initial O2 pressure). More importantly, these new supported ruthenium nanoparticles (Ru/ n ‐HT) show great durability throughout the reusability experiments.